Perbedaan Kinerja Mengajar Guru Ditinjau dari Peringkat Akreditasi Lembaga (Studi Komparatif di MAN 1 dan MAN 2 Sungai Penuh - Zebua, Ali Marzuki; Primanda, Oktavia (Prodi PAI STAI Sumatera Medan, 2020)
This study aims to determine differences in teacher teaching performance in terms of institutional accreditation rankings, with a focus on the factors that influence it. This research was carried out at MAN 1 and MAN 2 Sungai Penuh. This research uses quantitative research methods based on comparative studies. The sample in this study amounted to 85 people (45 teachers MAN 1 and 30 teachers MAN 2) taken from the total population (all teachers MAN 1 and 2 Sungai Penuh) of 123 people. Data collection techniques using questionnaires and documentation studies. Questionnaires to measure differences in teacher teaching performance, and documentation to gain insight into teacher institutions and performance so far. Hypothesis testing and significance level using the independent comparison formula t-test for two-way test. The results showed that there was a significant difference between the teaching performance of teachers at MAN 1 Sungai Penuh and MAN 2 Sungai Penuh. This can be seen from the results of the t-test calculation results t count 2.771 while t table 1.993. The results also show that the institution's accreditation ranking has a linearity impact on improving teacher performance, the accreditation ranking will increase based on good teacher performance.